2019
DOI: 10.1186/s13041-019-0506-8
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary wheel running promotes myelination in the motor cortex through Wnt signaling in mice

Abstract: Myelin of the central nervous system exhibits strong plasticity, and skill learning exercise promotes oligodendrogenesis and adaptive myelination. Increasing evidence shows that brain structures and functions are affected by physical activity. However, the impact of voluntary physical activity on central myelination and its underlying mechanism remains unclear. The present study aimed to investigate the effect of voluntary wheel running (VWR) on central oligodendrogenesis and adaptive myelination in mice. Adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…Post hoc analysis revealed that the total distance traveled were not changed in the mice subjected to treadmill running (vehicle + run) compared to the control mice (vehicle + static). This is in line with the previous research (Zheng et al, 2019). Schizophrenialike model mice (MK801 + static) showed hyperlocomotion compared to the control ones (vehicle + static).…”
Section: Treadmill Running Ameliorates Mk801-induced Behavioral Changessupporting
confidence: 93%
“…Post hoc analysis revealed that the total distance traveled were not changed in the mice subjected to treadmill running (vehicle + run) compared to the control mice (vehicle + static). This is in line with the previous research (Zheng et al, 2019). Schizophrenialike model mice (MK801 + static) showed hyperlocomotion compared to the control ones (vehicle + static).…”
Section: Treadmill Running Ameliorates Mk801-induced Behavioral Changessupporting
confidence: 93%
“…OFT and BWT were performed every 10 days for a total of 5 times (three times during weeks 1-5 and two times during weeks 6 and 7 having AT/vehicle treatment) during the experiment. BWT is a paradigm assessing sensorimotor balance and coordination ability ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, paradigms involving enrichment or deprivation of ll sensory or social input, such as social isolation, whisker stimulation, or monocular visual deprivation, have been shown to variously alter proliferation, differentiation, survival, and/or myelination by oligodendrocyte lineage cells (Bacmeister et al, 2020;Etxeberria et al, 2016;Fukui et al, 1991;Gyllensten and Malmfors, 1963;Hughes et al, 2018;Kato et al, 2020;Liu et al, 2012;Makinodan et al, 2012;Osanai et al, 2018;Sinclair et al, 2017;Swire et al, 2019;Tauber et al, 1980;Yang et al, 2013Yang et al, , 2020Zhao et al, 2011). The importance of experience-dependent myelination is particularly evidenced by studies showing that increased oligodendrogenesis evoked by motor, spatial, and fear-conditioning learning paradigms is necessary for proper learning and memory (McKenzie et al, 2014;Pan et al, 2020;Steadman et al, 2020;Wang et al, 2020;Xiao et al, 2016;Xin and Chan, 2020;Zheng et al, 2019;Zhou et al, 2020). Altogether, these studies convincingly demonstrate the capacity for experiential input and neuronal activity to shape oligodendroglia and myelin, but the precise cellular and molecular events underlying this plasticity are less well understood.…”
Section: Introduction To Myelin Plasticitymentioning
confidence: 99%